Integrated WDPI–WEAP Framework for Multi-Scenario Evaluation of Irrigation Water Delivery Performance: A Case Study of Wawotobi Irrigation System, Indonesia - Rindang Santiago Samudra Suwarjo; Sri Wahyuni; M. Amar Sajali (Jurnal Penelitian Pendidikan IPA, 2026)
The operational performance of aging irrigation infrastructure in tropical developing countries remains poorly understood at the zone level, since aggregate evaluation conceals inter-zonal disparities. This study evaluated the Wawotobi Irrigation System, a 42-year-old scheme served by Wawotobi Weir, encompassing 11,595 ha across five zones in Southeast Sulawesi, Indonesia, using an integrated Water Delivery Performance Index (WDPI) and Water Evaluation and Planning (WEAP) framework under normal-year (Q50) and dry-year (Q80) conditions. Zone-disaggregated evaluation revealed a composite WDPI of 0.39 (poor), with adequacy ranging from 0.31 to 0.79 and reliability as low as 0.00 in two zones. Sensitivity analysis identified intake withdrawal capacity as the dominant constraint on reliability (sensitivity index = 2.81), whereas transmission loss coefficients showed uniformly low sensitivity. Multi-scenario simulation showed that Intake Optimization achieved the highest performance (WDPI of 0.76 under Q50 and 0.56 under Q80), while Downstream Priority reallocation proved counterproductive, reducing equity from 0.58 to 0.10 under Q50 by withholding supply from lower-priority zones. A strong adequacy-reliability correlation (r = 0.91 under Q50) explains why intake-focused interventions outperform distributional adjustments alone, identifying intake capacity enhancement as the most effective strategy for improving irrigation performance in aging tropical systems.